Book review - Reynolds, Judith (Critical Studies in Teaching and Learning, 2025)
Clift, B.C., Costas Batlle, I., Bekker, S., & Chudzikowski, K. (Eds.). (2023). Qualitative Researcher Vulnerability: Negotiating, Experiencing and Embracing (1st ed.). Routledge. https://doi.org/10.4324/9781003349266